2016
DOI: 10.1007/s00259-016-3465-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of quantitative myocardial positron emission tomography for risk stratification in patients with hypertrophic cardiomyopathy: a 2016 reappraisal

Abstract: Dip-MBF confirms its role as potent predictor of outcome in HCM. However, the threshold for prediction in a contemporary cohort is higher than that reported in earlier studies. Dip-MBF impairment in the lateral wall, possibly reflecting diffuse disease extending to non-hypertrophic regions, is a sensitive predictor of mortality in HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…However, we additionally found that perfusion abnormalities could even be present in segments that were non-hypertrophied and contained no LGE 12 13. To our knowledge, this is the largest CMR quantitative perfusion study, with prior cohorts including 30–40 patients and similar to the largest quantitative PET study of 100 patients 28…”
Section: Discussionmentioning
confidence: 56%
“…However, we additionally found that perfusion abnormalities could even be present in segments that were non-hypertrophied and contained no LGE 12 13. To our knowledge, this is the largest CMR quantitative perfusion study, with prior cohorts including 30–40 patients and similar to the largest quantitative PET study of 100 patients 28…”
Section: Discussionmentioning
confidence: 56%
“…Positron emission tomography (PET) with either O 15 -labeled water or N 13 -labeled ammonia is the most reliable method for imaging myocardial blood flow (MBF) in HCM. 34,35 Measurements of MBF by PET at rest and during maximal vasodilation have demonstrated marked limitation of coronary flow reserve in patients with HCM in the absence of epicardial coronary artery disease, offering powerful evidence of microvascular dysfunction. 3 The relation of reduced MBF reserve and myocardial fibrosis using MRI has been well established in HCM.…”
Section: See Related Article Pp 1125-1134mentioning
confidence: 99%
“…3 The relation of reduced MBF reserve and myocardial fibrosis using MRI has been well established in HCM. [33][34][35] Indeed, the identification of significantly reduced MBF reserve by PET has been shown to be a powerful predictor of subsequent mortality in HCM. 34 Bravo has summarized the role of PET for detection of myocardial ischemia in HCM.…”
Section: See Related Article Pp 1125-1134mentioning
confidence: 99%
“…Castagnoli et al [ 12 ] explored the role of quantitative myocardial PET for risk stratification in patients with hypertrophic cardiomyopathy (HCM). MBF <1.1 mL/min/g following dipyridamole (Dip-MBF) assessed by PET was previously identified as an important outcome predictor in HCM, although such extreme Dip-MBF impairment is only rarely observed recently.…”
Section: Cardiology—quantitative Pet Assessment Of Myocardial Perfusimentioning
confidence: 99%